2021
DOI: 10.7150/ijbs.59725
|View full text |Cite
|
Sign up to set email alerts
|

Could protein content of Urinary Extracellular Vesicles be useful to detect Cirrhosis in Alcoholic Liver Disease?

Abstract: Alcohol abuse has a high impact on the mortality and morbidity related to a great number of diseases and is responsible for the development of alcoholic liver disease (ALD). It remains challenging to detect and evaluate its severity, which is crucial for prognosis. In this work, we studied if urinary EVs (uEVs) could serve in diagnose and evaluate cirrhosis in ALD. To this purpose, uEVs characterization by cryo-electron microscopy (Cryo-EM), Nanoparticle Tracking Analysis (NTA) and Western blotting (WB) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…EV size and concentration have been found to change in several liver disease settings indicating that EV-based liquid biopsy analysis can be employed for diagnostics, thus warranting further studies on the biological basis or functional relevance ( 31 ). For instance, it was shown that, in cirrhotic patients, there was an increase in size, concentration, and protein content of urinary EVs compared with controls ( 22 ). Moreover, Wetmore et al reported that the diameter of circulating EV increased in rodents after treatment with D-galactosamine, whereas Cho et al found an increased release of EV after incubation of mice and human hepatocyte cultures with acetaminophen, hence supporting our data ( 14 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…EV size and concentration have been found to change in several liver disease settings indicating that EV-based liquid biopsy analysis can be employed for diagnostics, thus warranting further studies on the biological basis or functional relevance ( 31 ). For instance, it was shown that, in cirrhotic patients, there was an increase in size, concentration, and protein content of urinary EVs compared with controls ( 22 ). Moreover, Wetmore et al reported that the diameter of circulating EV increased in rodents after treatment with D-galactosamine, whereas Cho et al found an increased release of EV after incubation of mice and human hepatocyte cultures with acetaminophen, hence supporting our data ( 14 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EVs are an excellent source for biomarkers. Several comprehensive analyses of EV proteins have been performed to detect liver cirrhosis biomarkers [ 31 33 ], but these studies have not evaluated EV protein changes due to stepwise fibrosis progression. We performed a comprehensive analysis of serum-derived EV proteins in chronic hepatitis C patients and clarified for the first time that SAP and PPBP in EVs could be markers of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption is a significant public health concern, leading to disabilities, poor health, and three million deaths every year. Excessive alcohol use accounts for 5.1% of the global disease burden (1). China has experienced the fastest-rising alcohol consumption in the world over the past few decades, which has been accompanied by significant increases in alcohol dependence and use disorders (2).…”
Section: Introductionmentioning
confidence: 99%